Clinical and molecular findings in a Chinese family with a de novo mitochondrial A1555G mutation - Ping Gu; Guojian Wang; Xue Gao; Dongyang Kang; Pu Dai; Shasha Huang (BMC, 2022)
Abstract Background The mitochondrial 12S rRNA A1555G mutation is the most prevalent deafness-causing mitochondrial DNA (mtDNA) mutation and is inherited maternally. Studies have suggested that A1555G mutations have multiple origins, although there is no direct evidence of this. Here, we identified a family with a de novo A1555G mutation. Method Based on detailed mtDNA analyses of the family members using next-generation sequencing with 1% sensitivity to mutated mtDNA, the level of heteroplasmy in terms of the A1555G mutation in blood DNA samples was quantified. Results An individual harbored a heterogeneous A1555G mutation, at 28.68% heteroplasmy. The individual's son was also a heterogeneous carrier, with 7.25% heteroplasmy. The individual's brother and mother did not carry the A1555G mutation, and both had less than 1% mitochondrial 12S rRNA A1555G heteroplasmy. Conclusion The A1555G mutation arose de novo in this family. This is the first report of a family with a de novo A1555G mutation, providing direct evidence of its multipoint origin. This is important for both diagnostic investigations and genetic counselling.